Rare cause of bilateral sudden deafness. (8th October 2016) - Vos, F I; Merkus, P; van Nieuwkerk, E B J; Hensen, E F
Abstract : In this paper, we describe the case of a 62-year-old female with recurring episodes of sudden deafness with vertigo and facial paresis. Within a month's time, this resulted in bilateral deafness and vestibular areflexia. Erroneously, the patient was diagnosed with sudden deafness of unknown origin and subsequently with neuroborreliosis (Lyme disease). The true diagnosis of relapsing polychondritis (RP) was revealed 9 months after initial presentation. The diagnostic delay is in part explained by the fact that, by definition, the disease has to relapse before the diagnosis can be made, but also by its pluriform clinical presentation. Timely identification of RP as the cause of this profound sensorineural hearing loss proved to be important. It was key in instigating adequate follow-up, and allowed for cochlear implantation before total cochlear obliteration, which might have hampered optimal hearing rehabilitation.